Distribution of Phytoplankton Types in Batujai Dam, Central Lombok Regency - Ayu Bintan Pratiwi; Dining Aidil Candri; Hilman Ahyadi; Mursal Ghazali; Tri Wahyu Setyaningrum (Jurnal Biologi Tropis, 2026)
Batujai Dam is the main dam in Central Lombok Regency which is used as a water source, irrigation area, flood control, freshwater fish farming, and the development of micro-hydro power plants. Batujai Dam is also a place of accumulation of polluted materials, domestic waste, agriculture and livestock. The purpose of this research was to determine the distribution of species, ecological indices, and environmental parameters in Batujai Dam. Determination of sample points using purposive sampling method in the fish cage area, water hyacinth, and open area. The phytoplankton community found was 48 species, 9 classes, and 22 families. The average species abundance was 38,575.18 ind/liter, the diversity index was 2.41, and the dominance index was 0.14. The waters of Batujai Dam are still relatively optimal for phytoplankton life.